Health Literacy and Administrative Factors Affecting the Coronavirus Disease 2019 Prevention and Control Performance of Village Health Volunteers at Muang District Chaiyaphum Province. - Wongwangchan, Kongkiat; Prasit, Nakarin; Nilnate, Nathakon (Journal of The Royal Thai Army Nurses, 2025)
The objective of this cross-sectional study was to investigate the health literacy and administrative factors affecting the coronavirus disease 2019 prevention and control performance of village health volunteers at Muang District Chaiyaphum province. The calculate the sample group in this study, 302 people were randomly sampled using a stratified random sampling method. The data was collected using a questionnaire. Statistics used to analyze data were descriptive statistics and inferential statistics, including Pearson’s correlation and stepwise multiple linear regression, with a significance level of 0.05. The results of the study revealed that the overall health literacy factors, administrative factors, and the coronavirus disease 2019 prevention and control performance of village health volunteers at Muang district Chaiyaphum province were at a high level with a mean of 2.53 (S.D.=0.30), 2.53 (S.D.=0.32) ,2.65 (S.D.=0.34), respectively. And, It was found that the overall of health literacy factors had a moderate level and administrative factors had a high-level relationship with the coronavirus disease 2019 prevention and control performance (r = .699, p-value = < .001) (r = .819, p-value = < .001), respectively. and found that health literacy factors; In terms of accessing health information and services, word-of-mouth communication, and decision-making and administrative factors in technology, time, and personnel able to jointly predict the coronavirus disease 2019 prevention and control performance of village health v¬-olunteers at Muang district Chaiyaphum at 85.0 (R2adj = .850)